Resignation of Regional Head and/or Vice in the Tenure: Politics of Law and Democracy Perspectives - Imam Ropii; Hibertus Sujiantoro (Jurnal Hukum Novelty, 2020)
Introduction to The Problem: The resignation of the regional head and/or vice today is a serious problem, both in the perspective of democracy, law, and even budget politics. Run as regional head and/or vice is a right, but maintaining the mandate after being elected is an obligation. It is compounded by the political direction of the law, which creates a pragmatically oriented political configuration, thus facilitating the resignation process. Of course, this atmosphere, in addition to injuring constituency, also contradicts democracy and the direction of its legal goal.Purpose/Objective Study: This research is based on two problem formulations, first, how is the regulation related to the resignation of the regional head and/or vice in the perspective of legal politics? Second, how are the resignation of the regional head and/or vice seen from a democratic perspective?Design/Methodology/Approach: This research uses a juridical-conceptual approach with a multidisciplinary method. The secondary data is analyzed qualitatively both on a juridical basis (legislation) and conceptually (democratic construction) so that the results will be obtained not only descriptive but also prescriptive.Findings: The regulations that are formed are still very pragmatic in the interests of the party. Therefore, the political configuration is still a preference to accommodate the rights and interests of political elites who seem oligarchic. Furthermore, this attitude of resignation also does not reflect the attitude of a democrat because it only focuses on his rights and annuls his obligations.Paper Type: Research Article